Religious Perspectives on Environmental Issues: A Dialogue with John Cobb - Sayem, Abu (Process studies, 2020)
This article is a transcription of a dialogue between Mohammad Abu Sayem and John Cobb that took place on June 24, 2019. The major topic covered in the dialogue is the relationship between Cobb's environmental thought and theology.